Painful Horner’s Syndrome and Its Association with Internal Carotid Artery Dissection - Ponte, Cássia Caroline Aguiar da; Rodrigues, Pedro Vitor Ferreira; Santos, Leonardo Elias Araujo dos; Lima, Maria Isabel Sales; Braga, Letícia Lôbo; Junior, Fernando Antonio Guimaraes; Santos, Ana Luiza Souza; Nunes, Leslie Mateus de Sousa; Castro, Júlia Viana de; Vasconcelos, Sophia Costa; Ribeiro, Rodrigo Mariano; Lucas Frigo; et al. (Headache Medicine, 2023)
Full abstract in PDF.